Potencialidades de polímeros hidroretentores para o meloeiro sob estresse salino - Lima, Luan Alves (2024)
Superabsorbent hydroretentive polymers (hydrogels) are promising for agriculture in semiarid regions affected by salinity and water deficit. However, depending on the type of hydrogel, salinity reduces its ability to retain moisture, compromising the use of these materials as soil conditioners. A previous laboratory study identified hydrogels that were more tolerant to salinity, but this occurred in the absence of soil. This research tested the hypothesis that this hydrogel, when mixed with soil and compared with other polymers more susceptible to salts, as well as with the absence of polymer, promotes greater water retention and favors the development of the melon tree under conditions of saline stress. The experiment was conducted in a greenhouse in Mossoró (RN), with a completely randomized design in a 3 x 4 + 1 factorial scheme, testing three hydrogels (H1, H2, H3), four levels of irrigation water salinity (0.5; 1.0; 2.0 and 4.0 dS m-1) and a control without hydrogel and saline water, with 5 repetitions. The soil water characteristic curve was evaluated at the matric potential points of 0, -6, -10, -33 -100 and -1500 kPa, water availability was calculated and measurements of growth and gas exchange of the melon tree subjected to the treatments were taken. The normality of the data was checked, followed by analysis of variance using the F test (p≤ 0.05). ANOVA, Tukey (p≤0.05) and Dunnet (p≤0.05) mean comparison tests for the qualitative treatment factor (type of hydrogel and control, respectively) and regression analysis for the quantitative treatment factor (salinity levels) were carried out. The H2 hydrogel resulted in 5.47%; 6.25%; 15.62% more water retained and 12.5% more water available in the soil under saline conditions compared to the H1, H3 and control treatments. The different responses of the hydrogels to salinity affected the photosynthetic rate quadratically for H1 and H2, and linearly for H3, with H2 showing a reduction up to 2.3 dS m-1 and standing out at EC 4.0 dSm-1 (9.66 (μmol CO2 m-2 s-1), Despite the reduction in water use efficiency (WUE), H2 proved to suffer less interference from the effects of salt stress, as evidenced by the improvement in stomatal conductance, transpiration and instantaneous carboxylation efficiency under adverse conditions. Salinity alone reduced stem diameter from 4.49 mm (0.5 dS m-1) to 3.45 mm (4 dSm-1); total dry mass with H2 showed a lower loss (20.50%) in relation to the lowest saline level and an increase in leaf area of 1433.99 (H1) and 1664.77 (H3) cm² plant-1. The H2 polymer is less affected by the effects of salinity and promotes greater water retention and favors the development of the melon tree under conditions of saline stress.